General structure design and field experiment of pneumatic rice direct-seeder - He, Xing; Zaiman, Wang; Xiwen, Luo; Xiaoman, Cao; Chunbo, Liu; Ying, Zang (International Journal of Agricultural and Biological Engineering, 2017)
In order to meet the requirement of field direct seeding for super hybrid rice: 1-3 seeds per hill, a pneumatic rice direct-seeder with six seeding metering devices was designed. Transmission system of pneumatic rice direct-seeder and seed metering device were analyzed in this study. And the pipeline structure and vortex pump were designed and selected. The pressure distribution of the pipeline was tested. The pressure value of each sub-pipeline under the conditions of different main pipeline pressure value was obtained and the reasons for pressure loss were analyzed. The results showed that the variation coefficient between sub-pipelines was less than 5%. The pipeline pressure could be evenly distributed. Further, the field experiments were carried out on super hybrid rice Peizataifeng using two-factor testing, by which the effects of different negative pressure and different forward speed (namely, rotational speed of suction plate) for seeding precision were studied. It found that: (1) the optimal negative pressure was 2 kPa; (2) under the optimal negative pressure, the probabilities of 1-3 seeds per hill for the direct-seeder were 93.41%, 95.47% and 97.50%, respectively, when the forward speed of the direct-seeded was high, medium and low speed; (3) the probability of empty hole was less than 2%, which satisfied the field direct seeding requirements of super hybrid rice. Additionally, hill spacing was measured, and the factors affecting the hill spacing were analyzed. The results showed that the fluctuation of hill spacing in the small range will not affect the seeding effect. In this study, a new type of pneumatic rice direct-seeder was designed. The main working components were tested and analyzed. The best parameters of field work were obtained. It provides the basis for the field application of the pneumatic rice precision seeder.Keywords: agricultural machinery, rice, pneumatic rice direct-seeder, field experiment, pipelineDOI: 10.25165/j.ijabe.20171006.3142Citation: Xing H, Wang Z M, Luo X W, Cao X M, Liu C B, Zang Y. General structure design and field experiment of pneumatic rice direct-seeder. Int J Agric & Biol Eng, 2017; 10(6): 31–42.